Flipping the curriculum for resident didactics: In-Training and certifying examination scores in an internal medicine residency - Luke McCoy; Ronald Markert; Elysha Thoms; Olivia Noall; Kathryn Burtson (PLoS ONE, 2025)
Purpose The flipped classroom (FC) model is increasingly used in undergraduate medical education, where it has been associated with improved knowledge acquisition. However, its impact on graduate medical education (GME) remains underexplored. We hypothesized that implementing a flipped didactics curriculum in our internal medicine residency program would improve performance on the Internal Medicine In-Training Examination (IM-ITE) and the American Board of Internal Medicine Certifying Examination (IM-CE). Methods In 2017, we transitioned from a traditional lecture-based (LB) curriculum to a flipped model. Noon conferences were replaced with problem-based learning (PBL) sessions three days per week, with additional active learning formats used on the remaining days. Morning reports were redesigned to deliver foundational content in advance of PBL sessions. The curriculum followed a 13-block annual structure aligned with ABIM content areas. We compared IM-ITE and IM-CE scores of residents who completed the full flipped curriculum to those trained under the prior LB model. Results We analyzed data from 279 residents who completed or were expected to complete training between 2014 and 2024. FC curriculum residents scored significantly higher on all three IM-ITE exams: ITE1 (62.39% vs. 59.53%, p = 0.008), ITE2 (69.78% vs. 66.54%, p = 0.002), and ITE3 (73.42% vs. 71.12%, p = 0.029). IM-CE scores did not significantly differ between groups (FC = 496 vs. LB = 481, p = 0.32). The first-attempt IM-CE pass rate was significantly higher among FC residents (95.5% vs. 84.0%, p = 0.012). Conclusions Residents in the flipped classroom curriculum demonstrated significantly higher IM-ITE scores and first-attempt pass rates on IM-CE compared to those in the lecture-based curriculum. These outcomes were associated with medium effect sizes, suggesting a meaningful educational benefit of the flipped classroom approach in graduate medical education.